Metropolitan Area Network Model Design Algorithm Using Regional Railways Information and Daily Movement Data for Beyond 5G Research - Koga Nakamura; Shotaro Kitano; Yusuke Hirota; Takehiro Tsuritani; Hiroshi Hasegawa; Takuji Tachibana (IEEE Access)
Metropolitan area networks (MANs) are crucial for establishing beyond 5G (B5G) infrastructure. Although regional railways information has been used to design MAN models, regional railways information is inadequate for designing the topology of metropolitan areas with underdeveloped railway lines. A MAN model algorithm using regional railways information and other regional data is necessary for designing the network models of many metropolitan areas. Therefore, we proposed a novel MAN model design algorithm that incorporates railroad route information and daily movement data to enhance B5G research. In the proposed algorithm, first, the topology is designed with the existing algorithm that incorporates only railway line information. Next, links are added in the topology according to the daily movement data such as person trip (PT) data. By using the proposed algorithm with daily movement data, the MAN model can be designed in metropolitan areas that are not completely covered by railways. We designed the Nara NMN39 model, Wakayama WMN30 model, and Fukui FMN17 model, for Nara, Wakayama, Fukui prefectures. There prefectures are not entirely covered by the railways in Japan. The designed MAN models are a simple plane graph and are widely used in numerous research domains. We compared the designed models with those developed using the existing algorithm that uses only railway line information. We confirmed that the proposed models could be used in various research applications. We provided insights into the characteristics of the proposed models to facilitate their use in research.